2019
DOI: 10.3390/medicina55050205
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyperbaric Oxygen at Different Pressures on Oxidative Stress and Antioxidant Status in Rats

Abstract: Background: The optimal use of oxygen at greater than atmospheric pressures in any operational or therapeutic application (hyperbaric oxygen, HBO2) requires awareness of the fact that the beneficial effects of oxygen coexist with toxic effects depending on the pressure and duration of exposure. In this study, we aimed to investigate the effect of HBO2 therapy on oxidative stress and antioxidant status in commonly used protocol for acute HBO2 indications, such as carbon monoxide intoxication, central retinal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
(55 reference statements)
4
13
1
Order By: Relevance
“…During HBO treatment (100% O 2 ), the PaO 2 in tissues rises to around 1500 mm Hg, which corresponds to pO 2 of 500 mm Hg in soft tissue and 200 mm Hg in bone [4]. It is well accepted that such exposure to high oxygen concentrations increases the formation of reactive oxygen species (ROS), which in turn results in consumption of antioxidants and reduction of antioxidant enzyme activity [40]. Furthermore, ROS can react with macromolecular components, inducing cells necrosis or apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…During HBO treatment (100% O 2 ), the PaO 2 in tissues rises to around 1500 mm Hg, which corresponds to pO 2 of 500 mm Hg in soft tissue and 200 mm Hg in bone [4]. It is well accepted that such exposure to high oxygen concentrations increases the formation of reactive oxygen species (ROS), which in turn results in consumption of antioxidants and reduction of antioxidant enzyme activity [40]. Furthermore, ROS can react with macromolecular components, inducing cells necrosis or apoptosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…HBO 2 reduced oxidative stress in an animal model of CO poisoning [26] and its beneficial effects included inhibition of leukocyte beta-2 integrins [18], reversal of CO-cytochrome c oxidase binding [27], and recovery of energy metabolism [28]. However, there have been reports that HBO 2 therapy itself induces oxidative stress [29][30][31][32]. Experimental data have shown that HBO 2 induces oxidative stress in healthy rat brains, measured as the lipid peroxidation products in brain cortex homogenates [29][30][31].…”
Section: Plos Onementioning
confidence: 99%
“…However, there have been reports that HBO 2 therapy itself induces oxidative stress [29][30][31][32]. Experimental data have shown that HBO 2 induces oxidative stress in healthy rat brains, measured as the lipid peroxidation products in brain cortex homogenates [29][30][31]. This HBO 2 -induced oxidative stress is related to the HBO 2 pressure [29] or the exposure time [30].…”
Section: Plos Onementioning
confidence: 99%
“…20 21 Moreover, HBO 2 -mediated alterations of the two antioxidants, heme oxygenase-1 (HO-1) and superoxide dismutase (SOD), have been demonstrated in experimental models of sepsis associated acute lung injury, in sepsis, and as part of a protective mechanism against oxidative DNA damage. [22][23][24][25][26][27] Multiple HBO 2 treatments have been shown to elevate RNS by enhancing production of nitrite+nitrate in selected cohorts, 28 but the systemic effect on RNS remains unresolved. 29 30 Of notable interest is a SODmediated regulatory function of NO expression 31 and an inhibitory function of HO-1 on the NO synthase expression, 32 indicating closely interconnected regulatory mechanisms between RNS and ROS.…”
Section: Original Researchmentioning
confidence: 99%